Murder in the Holy Place - Jenkins,Jerry B ; LaHaye, Tim and FABRY, CHRIS (Wheaton Tyndale House Publisher, 2003)
The Young Tribulation Force has its hands full as Judd and Lionel witness a terrible plane crash, leaving them unable to get back to Jerusalem, and as Vicki stands by a new believer in need of some help.
Keywords: Rapture (Christian eschatology) -- Good and evil -- Christian life